Hygiene Related Factors That Influence Teacher Turnover In Public Secondary Schools In Baringo District, Kenya - Chemwei, Bernard; Koech, Sharon Jerotich (Advances in Social Sciences Research Journal, 2015)
The increasing global rates of teacher turnover in the past few years have raised concern among education stakeholders than ever before. In Kenya, high employee turnover is a common occurrence in the teaching profession. The costs of teacher turnover are usually very high and can have significant financial implications on the government. Studies conducted in the field of management indicate that the character of human resource is highly influenced by two factors namely hygiene and motivational factors. These are the factors responsible for attracting suitable human resource and maintaining it. Indeed, these factors translate to an important aspect of job performance known as job satisfaction and job dissatisfaction. Job satisfaction is an essential element for the maintenance of the workforce numbers of any organization. This paper examines the hygiene related factors that influence turnover among teachers based on a study conducted in Baringo District secondary schools in Kenya. Hygiene related factors refer to the conditions surrounding the job which motivate or dissatisfy people at the work place. The Descriptive survey research design was used. All the 21 public secondary schools in Baringo district were used. The simple random sampling technique was employed to select 97 teachers out of the total population of the 329 Teachers’ Service Commission teachers in the district to participate in the study. Data was collected by the use of a questionnaire and an interview schedule. The data collected were analyzed using both descriptive and inferential statistics and will are presented in the form of frequencies, tables, percentages, pie charts, and bar graphs. In addition, the Pearson Moment Correlation was used to analyze the relationship between personal factors and teacher turnover intentions. It was established that teachers’ dissatisfaction with salaries, working for the same employer for too long and communication-related issues at work informed their intentions to quit work. It was thus recommended that the government through the teachers’ service commission (TSC) should harmonize teachers’ salaries and allowances with those of other sectors in the government. In addition, teachers should be given allowances such as leave and commuter as well as other benefits such as medical insurance. From the study, the ministry of education (MOE) and TSC may use the findings to develop policies that will make teaching more attractive. Similarly, they can draw useful lessons on staffing issues in the teaching profession and can use the findings to guide school managers to recruit the right calibre of teachers who can stay longer in the profession.